Factors related to the early and late success of direct current cardioversion of chronic nonrheumatic atrial fibrillation: An echocardiographic study - Szulc, Marcin (Pulsus Group Inc, 2001)
OBJECTIVES: To assess factors related to the success of restoration and one-year maintenance of sinus rhythm in chronic (more than 48 h) nonrheumatic atrial fibrillation (AF). METHODS AND RESULTS: One hundred and fifty consecutive patients aged 62±9 years with AF lasting 123±254 days were evaluated clinically with transthoracic and transesophageal echocardiography before elective direct current cardioversion. Heart chamber dimensions and left ventricular ejection fraction were measured. The presence of left atrial thrombi and spontaneous echocardiographic contrast as well as flow velocities in the left atrial appendage were assessed. The first cardioversion was followed by standardized two-step antiarrhythmic treatment including a second cardioversion, if necessary. Twenty patients (13%) spontaneously reverted to sinus rhythm (S) during anticoagulation preceding cardioversion, 81 (54%) were successfully cardioverted (Y), and in 49 (33%) cardioversion failed initially (N). No differences were noted between the two latter groups. However, S patients had smaller left atria measured in the short and long axes (42±4 mm, P=0.05, and 53±7 mm, P=0.005, respectively) than both the Y (45±4 and 61±8 mm) and the N patients (46±4 and 61±8 mm). One-year follow-up was obtained in 95 patients: 64 (67%) were in sinus rhythm while 31 (33%) had AF. Again, no initial differences predicting the maintenance of sinus rhythm were found. CONCLUSIONS: Spontaneous reversion of AF seems more likely with smaller left atria. Echocardiography, including trans-esophageal echocardiography, is unlikely to identify patients in whom attempts to restore and maintain sinus rhythm will fail or succeed.